The Development of Adolescent Online Reading Literacy Assessments - Kuei-Lin Chang (National Taipei University of Education, 2013)
By adopting the constructs of reading literacy and with the use of information and communication technology, the purpose of this study is to develop two adolescent online reading literacy assessments (ORLA) and examine the preliminary validity of ORLA. In addition, samples of online reading literacy performance are described. The design of ORLA is based on PISA electronic reading assessment framework and Leu et al. (2004)'s online reading comprehension definition. A total of 601 eighth graders from junior high schools and 618 tenth graders from senior high schools in Taiwan City participated in this study. This study uses Rasch IRT model to calibrate the item parameter and scale scores. The results indicated: the online reading literacy assessments had adequate difficulty level, reasonable validity evidences, and students' online reading literacy performance contains ICT element which is different from offline reading; the gender effect exists in the online reading environment by grades.